Whole-being Framework - Marea Saldarriaga (Cubic Journal)
The Whole-being © framework was developed as a starting point for a holistic coaching approach, devised in the pursuit of a meaningful way to thrive both in our personal and professional lives. It is only when people are whole that a world based on integrity, freedom, kindness and compassion can materialize. This paper is aligned to the perspective of!experiences, specifically addressing the role design has in helping organisations understand what really drives their employees, while bringing attention to the “whole-being ecosystem” which influences people’s motivation and performance. A whole-system approach is necessary so that executives can thrive without running the risk of burning out. Policies must align themselves in the direction of this purpose, to create the right conditions for “whole-beings” to thrive, but in the midst of all of this self-awareness remains essential for the system to work. The training focuses on optimizing the participant’s energy as well as on developing certain attributes to feel and be whole.